SEASONAL VARIATIONS IN SEMEN PRODUCTION OF MURRAH BUFFALO BULLS - TIWARl, RITESH; MISHRA, G K; SHUKLA, M K; SINGH, R B; SAXENA, S K; SIDDIQUl, M U (The Indian Journal of Animal Reproduction, 2023)
Total of 4834 ejaculates collected from seven Murrah buffalo bulls were studied to observe the effect ofseasons on semen quality, freezibility and loss of male gametes during frozen semen production. Mean values forseminal parameters viz. number of ejaculates per month, seminal volume ( ml), initial motility (% ), sperm concentration(106/ml), sperm output per ejaculate (million} and post-thaw motility(%) were 14.38, 3.12 ± 0.02, 67.42 ± 0.07,1139.71 ± 5.89, 3487.59 ± 28.58 and 53.68 ± 0.08 respectively. Sperm concentration, initial and post-thaw spermmotility differed significantly (P
Keywords: Murrah; Seminal characteristics; Seasons